2020
DOI: 10.3390/ijgi9120702
|View full text |Cite
|
Sign up to set email alerts
|

Applying GIS and Text Mining Methods to Twitter Data to Explore the Spatiotemporal Patterns of Topics of Interest in Kuwait

Abstract: Researchers have developed various approaches for exploring the spatial information, temporal patterns, and Twitter content in topics of interest in order to generate a better understanding of human behavior; however, few investigations have integrated these three dimensions simultaneously. This study analyzes the content of tweets in order to conduct a spatiotemporal exploration of the main topics of interest in Kuwait in order to provide a deeper understanding of the topics people think about, when they thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, we did not investigate whether there is a statistical difference between GUs with high and low number of geotagged tweets. Future work could address these limitations by utilizing methods to infer demographic information such as the gender of users (e.g., analyzing the name of users), analyzing non-English tweets, studying other types of location Twitter sharing strategies, such as place-tagging, investigating differences regarding different times and locations, exploring categories of GUs based on the number of geotagged tweets, and analyzing special and temporal factors such as spatiotemporal analysis of tweets [74]. It would also be interesting to expand this study by comparing users based on their county (e.g., GUs vs. NGUs in Canada or France).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not investigate whether there is a statistical difference between GUs with high and low number of geotagged tweets. Future work could address these limitations by utilizing methods to infer demographic information such as the gender of users (e.g., analyzing the name of users), analyzing non-English tweets, studying other types of location Twitter sharing strategies, such as place-tagging, investigating differences regarding different times and locations, exploring categories of GUs based on the number of geotagged tweets, and analyzing special and temporal factors such as spatiotemporal analysis of tweets [74]. It would also be interesting to expand this study by comparing users based on their county (e.g., GUs vs. NGUs in Canada or France).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have also applied bibliometric theories to track topics and influencing factors in research fields by analyzing high-frequency keywords and specialized terms [19][20][21]. Furthermore, some researchers utilize web crawlers to obtain word frequency data from online forums and analyze the most frequent words to capture the main issues discussed in those forums [22][23][24]. This method can quickly reveal the evolution of topics in a specific discipline.…”
Section: Literature Review 21 Development and Academic Application Of...mentioning
confidence: 99%
“…We have found that there is a gap in the field of natural language processing for the Kuwaiti dialect; there is limited availability of linguistic resources for this dialect, with only a few published research papers in the field of NLP focusing on it [14][15][16][17].…”
Section: Natural Language Processing (Nlp) Of Kuwaiti Dialectmentioning
confidence: 99%